"At‐risk" kidney: How surgical factors influence renal functional preservation after partial nephrectomy. (25th February 2019) - Dagenais, Julien; Bertolo, Riccardo; Garisto, Juan; Chavali, Jaya; Kaouk, Jihad
Abstract : Objectives: To investigate the influence of surgical modifiable factors on chronic kidney disease upstaging in a contemporary cohort of patients with normal and "at‐risk" kidneys undergoing partial nephrectomy. Methods: We reviewed 778 consecutive patients with ( n  = 634)/without ( n  = 144) chronic kidney disease or risk factors for chronic kidney disease in our institutional partial nephrectomy database. Chronic kidney disease upstaging was assessed using glomerular filtration rate measurements preoperatively and at 3–12 months postoperatively. Using a multivariate logistic regression, baseline clinicodemographic factors, and the operative measurements of excisional volume loss and warm and cold ischemia time on rates of chronic kidney disease upstaging were determined. Marginal effects were used to analyze the impact of ischemia time and generate interaction curves. Results: Chronic kidney disease/risk factors for chronic kidney disease had equivalent rates of chronic kidney disease upstaging as the healthy kidney cohort (31.5% vs 38.2%, P  = 0.15). Of the entire cohort, 2.8% were upstaged to stage IV–V chronic kidney disease. Multivariate analysis found a significant association between chronic kidney disease upstaging and excisional volume loss in both cohorts (no chronic kidney disease/risk factors for chronic kidney disease: odds ratio 1.63, P  = 0.04; chronic kidney disease/risk factors for chronic kidney disease: odds ratio 1.42, P  = 0.001). Only in the chronic kidney disease/risk factors for chronic kidney disease cohort, there was an association between ischemia type/duration and chronic kidney disease upstaging (odds ratio 1.04, P  = 0.04). Warm ischemia began to predict an increased risk of chronic kidney disease upstaging at 17.6 min, which became statistically significant at 49 min. Conclusions: Chronic kidney disease upstaging is common after partial nephrectomy. Although volume loss unequivocally affects rates of upstaging irrespective of baseline renal function, warm ischemia time disproportionately influences "at‐risk" kidneys. Therefore, strong consideration should be given to minimizing volume loss and using cold ischemia when extended clamp times are anticipated in "at‐risk" kidneys.